The Effectiveness of Tiktok Application on the Secondary School Students’ English Vocabulary Development. - Zalza Putri Nabila; Baso Jabu; Ahmad Talib (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
The objective of this research is to find out whether TikTok Application is effective to develop secondary school students’ vocabulary. This research adapts Pre-Experimental design by using Pre-test and Post-test to measure students' vocabulary abilities before and after the treatment where students are shown English vocabulary learning content for 4 weeks. It was conducted in SMP Kartika XX-2 Makassar and there were 22 students from class IX B who were the samples in this study. The research findings show that the mean Pre-test score is 55.00 where there are only 5 students who get the Good score category. Meanwhile, the mean score from the Post-test is 82.50 and students who obtained the Very Good - Good score category increase to 21 people. Based on this data, it can be concluded that the TikTok application is effective in developing students' English vocabulary with an improvement of 50%.Keywords—TikTok Application, Vocabulary Development